Effect of suction on the MHD flow in a doubly-stratified micropolar fluid over a shrinking sheet - Khashi’ie, N. S.; Wahi, N.; Arifin, N. M.; Ghani, A. A.; Hamzah, K. B. (Lviv Polytechnic National University, 2022)
This paper investigates the influence of suction on the flow, heat and mass transfer characteristics over a permeable shrinking sheet immersed in a doubly stratified micropolar fluid. The model which consists of partial differential equations is converted into a set of nonlinear equations using similarity transformations and then solved using the bvp4c solver. Numerical results obtained are presented graphically for the distributions of velocity, angular velocity, temperature and concentration profiles within the boundary layer for various values of the magnetic parameter and wall mass suction parameter. It is visualized that the enhancement of suction parameter will increase the skin friction, heat transfer rate (local Nusselt number) and Sherwood number. It is also found that as the magnetic parameter increase, there is an increment in the skin friction while opposite results are obtained for the local Nusselt number and Sherwood number.